Premedication with corticosteroids does not impact the pharmacokinetics of infliximab in inflammatory bowel disease irrespective of azathioprine cotreatment. Issue 8 (August 2019) - Larsen, Lone; Jess, Tine; Drewes, Asbjørn M.; Dige, Anders; Fallingborg, Jan; Jacobsen, Bent A.; Aagaard, Bitten; Agnholt, Jørgen
Abstract : Objective: Loss of infliximab (IFX) effect is a clinical challenge in the management of patients with Crohn's disease (CD), but this can potentially be reduced with azathioprine (AZA) or with corticosteroids (CS). We aimed to study whether CS premedication with or without cotreatment with AZA could reduce antibody formation and affect the IFX elimination rate. Patients and methods: A cross-sectional observational study was conducted at two centers with CD patients receiving maintenance IFX therapy for 12–18 months. In addition to IFX, patients received either CS premedication or not, with or without concominant AZA. Results: Fifty-seven patients were included in the study. Thirty-one patients received premedication with CSs, and 11 (35.5%) of these also received AZA, whereas this was the case for 22 of 26 (84.6%) patients in the non-CS group. No difference in IFX trough level ( P =0.10) or halftime elimination ( P =0.31) was observed with or without CS premedication. Concomitant AZA was associated with significantly longer mean half-life of IFX ( P =0.04). Total IFX antibody concentrations were 15.8 and 12.9 with and without CS, respectively, in those not receiving AZA versus 4.3 and 6.1 AU/ml with and without CS, respectively, in those receiving AZA ( P =0.004). Premedication with CS did not have any effect on the frequency of antibody formation ( P =0.28). Conclusion: In patients with CD and in maintenance IFX therapy, premedication with CS did not influence antibody formation, IFX trough levels or IFX halftime elimination, irrespective of concomitant AZA use. However, the use of AZA was associated with higher IFX trough levels and lower total IFX antibody concentrations.